Diagnosis Laboratorium pada COVID-19 - Nabil Salim Ambar (PROCEEDING UMSURABAYA, 2020)
AbstractCOVID-19 (corona virus disease -19) is a respiratory tract infection caused by the SARS-CoV-2 coronavirus. The spread of this virus is so fast that, even though the cure rate is high, thefatality rate is equally high. Controling of Corona virus transmission can be done by breakingthe chain of transmission, examining for tracking, tracing people who have had contact withsufferers, and examining for diagnosis (testing) of COVID-19 cases. One of the functions ofthe COVID-19 laboratory examination is for diagnosis. Laboratory examination parametersthat are often used for the diagnosis of COVID-19 are: Whole Blood, C-Reactive Protein(CRP), Antibody Rapid Test and RT-PCR. However, the gold standard for COVID-19diagnosis is RT-PCR. The purpose of this literature review is to provide an insight into aprecise, fast, and highly accurate diagnosis in order to immediately mitigate and prevent anyspike in COVID-19 cases.Keywords : diagnosis of COVID-19, hematology examination, antibody rapid test, RT-PCR